The response of peripheral microcirculation to gravity-induced changes. (August 2018) - Ovadia-Blechman, Zehava; Gritzman, Ashley; Shuvi, Maya; Gavish, Benjamin; Aharonson, Vered; Rabin, Neta
Abstract: Background: The peripheral microcirculation supplies fresh blood to the small blood vessels, providing oxygen and nutrients to the tissues, removing waste, and maintaining normal homeostatic conditions. The goal of this study was to characterize the response of the peripheral microcirculation, in terms of blood flow and tissue oxygenation variables, to gravity-induced changes. Methods: The study included 20 healthy volunteers and the experiment involved monitoring central and peripheral variables with the right hand positioned at different heights. These positions correspond to various gravitational levels. Peripheral perfusion and oxygenation were monitored using a laser Doppler flowmeter, photoplethysmograph, and transcutaneous oxygen tension monitor. Local blood pressure and respiration rate were also measured. Findings: At the heart level, tissue oxygenation displayed a nadir, while capillary flow displayed a peak. Similar but weaker changes were observed at the control hand. In contrast, the photoplethysmograph's amplitude strongly decreased upon reducing the arm position below heart level. Both systolic and diastolic pressures decreased linearly between the highest to lowest arm position. Interpretation: The results may reflect peripheral compensation mechanisms, as well as an interaction between the central and peripheral cardiovascular systems, in response to local changes in blood pressure. The observed dependence of the oxygenation pattern on height could lead to important new insights for the diagnosis and treatment of problems in the regulation of tissue perfusion. Highlights: Local compensation mechanisms, due to local blood pressure changes, are presented. Interactions between the peripheral and central systems are described. Tissue oxygenation displayed strong dependence on hand height. A bilateral effect was observed in response to a unilateral change in pressure. The results may have impact on the clinical treatment of limb injuries.